Making Mice : Standardizing Animals for American Biomedical Research, 1900-1955 (Book collections on Project MUSE., 2004)
"Throughout Making Mice, Karen Rader explains how the story of mouse research illuminates our understanding of key issues in the history of science such as the role of model organisms in furthering scientific thought. Ultimately genetically standardized mice became icons of standardization in biomedicine by successfully negotiating the tension between the natural and the man-made in experimental practice." "This book will appeal not only to historians of science but also to biologists and medical researchers"--